2012
DOI: 10.1111/j.1365-2044.2011.06995.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of sugammadex in the development and modification of an allergic response to rocuronium: evidence from a cutaneous model*

Abstract: SummaryThe availability of sugammadex as a selective encapsulating agent for rocuronium has led to speculation that it may be useful in mitigating rocuronium-induced anaphylaxis. Off-label use of sugammadex for this indication has already been documented in case reports although there are theoretical objections to the likelihood of an allergen-binding agent's being able to attenuate the immunological cascade of anaphylaxis. Using a cutaneous model of anaphylaxis in rocuronium-sensitised patients, we were unabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 23 publications
(33 reference statements)
1
58
2
5
Order By: Relevance
“…Our findings gave us no alternative but to conclude that 'sugammadex is unlikely to modify significantly the clinical course of an established allergic reaction', as they do not support a role for sugammadex in the modification of an established allergic response [1]. Baldo cites several case reports that suggest a role for sugammadex in modifying an allergic response, but none of these prove a role, because anaphylaxis varies in its severity and is self-terminating in most cases, and there are plausible alternative explanations in each case [1].…”
Section: A Replycontrasting
confidence: 65%
See 1 more Smart Citation
“…Our findings gave us no alternative but to conclude that 'sugammadex is unlikely to modify significantly the clinical course of an established allergic reaction', as they do not support a role for sugammadex in the modification of an established allergic response [1]. Baldo cites several case reports that suggest a role for sugammadex in modifying an allergic response, but none of these prove a role, because anaphylaxis varies in its severity and is self-terminating in most cases, and there are plausible alternative explanations in each case [1].…”
Section: A Replycontrasting
confidence: 65%
“…We read with great interest the metaanalysis of Yin and Ho regarding the use of plethysmographic variability index (PVI) to predict fluid responsiveness [1]. The authors concluded that PVI had a reasonable ability to predict preload responsiveness in peri-operative patients.…”
Section: A Replymentioning
confidence: 99%
“…Their and our similar results support that sugammadex gives similar muscle responses in trachea and bronchus. In addition, laryngospasm ,bronchospasm and anaphylaxis related sugammadex were reported in a few clinical data [16][17][18][19][20][21][22][23][24][25][26][27]. Absence of tracheal tissue response in our study suggests that these clinical conditions related with other mechanisms except the tracheal tissue response.…”
Section: Discussionsupporting
confidence: 50%
“…We were interested to read about the effects of rocuronium and sugammadex on rat livers by Tomak et al [1], but are concerned that they misrepresented the findings of the study by Clarke et al [2] who used an in-vivo human model of IgEmediated anaphylaxis that demonstrated that patients were anergic to sugammadex-bound rocuronium. However, there was no attenuation in the wheal-and-flare response when sugammadex was administered after the reaction had commenced.…”
mentioning
confidence: 99%